2017
DOI: 10.1039/c7cp02969a
|View full text |Cite
|
Sign up to set email alerts
|

A water-mediated and substrate-assisted aminoacylation mechanism in the discriminating aminoacyl-tRNA synthetase GlnRS and non-discriminating GluRS

Abstract: Glutaminyl-tRNA synthetase (GlnRS) catalyzes the aminoacylation of glutamine to the corresponding tRNA. However, most bacteria and all archaea lack GlnRS and thus an indirect noncanonical aminoacylation is required. With the assistance of a non-discriminating version of Glutamyl-tRNA synthetases (ND-GluRS) the tRNA is misaminoacylated by glutamate. In this study, we have computationally investigated the aminoacylation mechanism in GlnRS and ND-GluRS employing Molecular Dynamics (MD) simulations, Quantum Mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…We further suggested that the ribozymal mechanism that we discovered is common in the editing reaction of various aaRS systems beyond the classes ( Table 1) [63]. In fact, Thermus thermophilus IleRS (class Ia) [77], Pyrococcus abyssi ThrRS (class IIa) [72,74,75,78], and Enterococcus faecalis ProRS (class IIa) [71] showed the similar binding mode of the nucleophilic water in the catalytic site. Furthermore, Kumar et al also suggested that the editing reaction of the complex of prolyl-tRNA synthetase (ProRS) and alanyl-tRNA Pro exhibited a similar mechanism, in which the 2 0 -OH group of A76 of tRNA Pro was involved in the substrate binding and the activation of the nucleophilic water [71].…”
Section: Ab Initio Qm/mm MD Simulation Of Editing Reactionmentioning
confidence: 67%
“…We further suggested that the ribozymal mechanism that we discovered is common in the editing reaction of various aaRS systems beyond the classes ( Table 1) [63]. In fact, Thermus thermophilus IleRS (class Ia) [77], Pyrococcus abyssi ThrRS (class IIa) [72,74,75,78], and Enterococcus faecalis ProRS (class IIa) [71] showed the similar binding mode of the nucleophilic water in the catalytic site. Furthermore, Kumar et al also suggested that the editing reaction of the complex of prolyl-tRNA synthetase (ProRS) and alanyl-tRNA Pro exhibited a similar mechanism, in which the 2 0 -OH group of A76 of tRNA Pro was involved in the substrate binding and the activation of the nucleophilic water [71].…”
Section: Ab Initio Qm/mm MD Simulation Of Editing Reactionmentioning
confidence: 67%
“…In the porphyrin/chlorophyll category, GLUTAM-ATE-TRNA LIGASE (GluRS), MAGNESIUM-CHELAT ASE SUBUNIT CHLI (GUN4) and DIVINYL CHLORO-PHYLLIDE A 8-VINYL-REDUCTASE (DVR) genes showed upregulation under white light. These genes localize in the chloroplast and are involved in the biosynthesis of chlorophyll and heme molecules, essential for light-harvesting and energy transduction in photosynthesis and the cell growth [41][42][43][44]. The flavonoids are thought to participate in protecting the photosynthetic apparatus against photoinhibition under excessive light [45].…”
Section: Discussionmentioning
confidence: 99%
“…Using MOE and the NAMD program, we submitted the resulting minimized model for unconstrained 10 ns MD simulation with a time step of 2 fs under constant pressure and temperature until the system reached equilibrium using a protocol we have successfully used in related studies. It is noted that the default settings of MOE were used, which includes use of the PME method for calculating Coulombic interactions, cutoffs for nonbonded long-range interactions of between 8 and 10 Å, and tether ranges from 0 to 100 Å applied to all heavy atoms. Furthermore, the standard protocol that is encoded in MOE was used to parametrize any ligands using the Amber12 force field.…”
Section: Computational Methodsmentioning
confidence: 99%